2007
DOI: 10.1073/pnas.0701981104
|View full text |Cite|
|
Sign up to set email alerts
|

Kruppel-like factor 15 is a regulator of cardiomyocyte hypertrophy

Abstract: Cardiac hypertrophy is a common response to injury and hemodynamic stress and an important harbinger of heart failure and death. Herein, we identify the Kruppel-like factor 15 (KLF15) as an inhibitor of cardiac hypertrophy. Myocardial expression of KLF15 is reduced in rodent models of hypertrophy and in biopsy samples from patients with pressure-overload induced by chronic valvular aortic stenosis. Overexpression of KLF15 in neonatal rat ventricular cardiomyocytes inhibits cell size, protein synthesis and hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
232
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(241 citation statements)
references
References 49 publications
9
232
0
Order By: Relevance
“…1C). Conversely, KLF15 has been shown to be substantially down-regulated in rodent models of heart failure (20,21), a pathologic state where myocardial lipid utilization is reduced (5,6). Consistent with this rodent data, we found KLF15 to be significantly reduced in failing human hearts with a significant recovery of expression after mechanical unloading with a left ventricular assist device (Fig.…”
Section: Klf15 Regulates Myocardial Lipid Utilization-becausesupporting
confidence: 78%
See 3 more Smart Citations
“…1C). Conversely, KLF15 has been shown to be substantially down-regulated in rodent models of heart failure (20,21), a pathologic state where myocardial lipid utilization is reduced (5,6). Consistent with this rodent data, we found KLF15 to be significantly reduced in failing human hearts with a significant recovery of expression after mechanical unloading with a left ventricular assist device (Fig.…”
Section: Klf15 Regulates Myocardial Lipid Utilization-becausesupporting
confidence: 78%
“…Plasmids and Adenoviruses-Expression plasmids containing the mouse KLF15 cDNA have been described previously (20). The Ϫ1.2 kb promoter region of mouse Slc27a1 (Fatp1) was PCR-amplified from purified genomic DNA (Promega) and subcloned into pGL3-basic (Promega).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inactivation of Klf15 resulted in a modest but significant increase in lean mass that was associated with a reduced expression of multiple genes encoding amino acid-degrading enzymes, including Bcat2 (8). However, a more recent study from this same group reported no change in skeletal muscle mass (9), while Klf15 null mice developed a severe cardiac hypertrophy in response to pressure overload (6). Alternatively, Klf15 overexpression was shown to accelerate catabolism of BCAA, resulting in myotube and skeletal muscle atrophy (28).…”
Section: Discussionmentioning
confidence: 99%